Bioluminescent Most-Probable-Number Method To Enumerate lux-Marked Pseudomonas aeruginosa UG2Lr in Soil - Flemming, C. A. (1994)
Bioluminescence measured with a luminometer and charge-coupled device was an effective marker in most-probable-number assays for luxAB-marked Pseudomonas aeruginosa UG2Lr in soil. Most-probable-number assays with microtiter plate wells and luminometer tubes gave estimates for UG2Lr that were similar to viable colony counts. Both methods detected five cells per g of soil.